2014
DOI: 10.1017/s1368980014000688
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Spanish dietary guidelines and its association with obesity in the European Prospective Investigation into Cancer and Nutrition (EPIC)-Granada study

Abstract: These findings support that the Spanish dietary guidelines might be an effective tool for obesity prevention. However, prospective studies investigating this association are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Changes in food choices were consistent with results from other studies in which higher diet quality scores reflected lower consumption of meat [5,65,66], alcohol [33,67] and discretionary food items [29,31]. The observed increased consumption of fruit (found with APDQS and DQT), non-starchy vegetables (found with DQT), tomato and other vegetables (found with APDQS) was also congruent with other studies associating higher intakes of vegetables and fruits associated with high diet quality [65,66].…”
Section: Changes In Food Choicessupporting
confidence: 90%
See 1 more Smart Citation
“…Changes in food choices were consistent with results from other studies in which higher diet quality scores reflected lower consumption of meat [5,65,66], alcohol [33,67] and discretionary food items [29,31]. The observed increased consumption of fruit (found with APDQS and DQT), non-starchy vegetables (found with DQT), tomato and other vegetables (found with APDQS) was also congruent with other studies associating higher intakes of vegetables and fruits associated with high diet quality [65,66].…”
Section: Changes In Food Choicessupporting
confidence: 90%
“…Several reviews [12,14,[23][24][25][26][27] have identified multiple DQIs that vary in design and the referent food or nutrient characteristics. DQIs tend to be applied in epidemiological studies to establish diet-disease links, characterise patterns of food consumption or evaluate adherence to country-specific dietary guidelines [28][29][30][31]. Characteristically, they are developed with reference to dietary guidelines, utilising an a priori approach [16].…”
Section: Introductionmentioning
confidence: 99%
“…Obese individuals consume larger quantities of food than normal individuals 36,37 and are less prone to changes in dietary behaviour 38 . Obesity levels are inversely associated with adherence to guidelines 39,40 , suggesting that obese subjects might be less prone to adhere to healthy eating and thus to prevent diet-related diseases.…”
Section: Determinants Of Change In Compliance To Dietary Guidelinesmentioning
confidence: 99%
“…Nevertheless, the percentage of TCC from simple sugars was above the recommendations [18,19], which is described that, independently the mechanisms by which the sugar intake might promote weight gain by increasing energy consumption to an extent that exceeds energy output and distorts energy balance [32], the increased consumption of simple sugar increase hyperinsulinaemia [33]. In addition, total fiber was less than previously described in same region population [30,34], and soluble fiber in particular was below the recommendations [35,36].…”
Section: Discussionmentioning
confidence: 82%